Teacher's Competences - Prospects for Development and Professional Training - Elżbieta Jaszczyszyn; Andrzej Cichocki (Ignatianum University Press, 2018)
After brief remarks related to the current discourse present in the professional literature on the perspective of the development of competences and professional improvement, this text focuses on ideas which have important implications for their perspective of development and the assessment of the process of professional improvement of teachers, namely (a) building teachers' professionalism, especially for those who are trapped in an increasingly formalized system, based on documents, content of teachers training courses and then in a rigid career path and (b) defining and assessing the standards of the professional development process. The text ends with the thesis that the most valuable resources available in each school are the teachers, that there is an urgent need to remodel the current system and to concentrate on strengthening the potential present in the idea of the professionalization of teachers (and their assessment) in terms of teaching standards (related to what they should know and be able to do).